Quality Human Resources in Lam Dong and the Issues Posed - Vu, Thi Thuy Dung (H. : ĐHQGHN, 2020)
Lam Dong is evaluated as a potential province in socio-economic development in the Central Highlands for many years. The development speed of Lam Dong contributes significantly to the development speed of the Central Highlands and the whole country. Contributing to that growth, we must mention Lam Dong's strategy of investing in the quality of human resources. More specifically, the input of high quality human resources based on local strengths is the fast, strong and sustainable direction of Lam Dong in recent years. This paper focuses on analyzing and evaluating the quality of human resources in Lam Dong in three aspects considered to be "three specialties" of Lam Dong which are human resources in the field of high-tech agriculture and human resources. in the field of tourism services and human resources for ethnic minorities. Since then, the article proposes solutions directions in the strategy for developing human resources, especially high quality human resources of Lam Dong in the future.